Delivery strategy of mass annual single dose DEC administration to eliminate lymphatic filariasis in the urban areas of Pondicherry, South India: 5 years of experience - Nandha, B (BioMed Central, 2007)
BACKGROUND: The recommended strategy for elimination of Lymphatic filariasis is single-dose, once-yearly mass treatment with anti-filarial drugs and the program is in operation on a national level in India. Rate of coverage and consumption is the most crucial factor in the success of Mass Drug Administration (MDA) program. In spite of massive efforts, the program demonstrated sub-optimal coverage and consumption in urban areas than rural. The involvement of Anganwadi workers (AWWs) of the Integrated Child Development Scheme (ICDS) as communicators and drug distributors was attempted to enhance the coverage and consumption in urban areas and the results presented here. METHODS: An annual single dose MDA program was launched under the auspices of Freedom From Filariasis (FFF) program in Pondicherry, India, in the year 1997 and continued for five years. A questionnaire survey was carried out following all the treatment rounds (TRs) for assessing coverage of distribution and consumption Five percent of randomly selected households constituted the sample. All the members available in the selected household at the time of interview formed the respondent of the study. RESULTS: The coverage of drug distribution during the TRs varied from 74.3 to 95.4 percent and consumption rate from 52.9 to 78.8. Among the respondents, 71% were aware of the MDA program and the source of information for 62.8% of them was through personal communication by the AWW. It was observed that 33.2% of the respondents who accepted the drug did so based on the trust on the AWW as a government representative. The main reason for non-consumption in all TRs was fear of side reaction (25.4 – 42.2%). CONCLUSION: The delivery-strategy of health information and Diethylcarbamazine (DEC) drug to the urban community using the AWWs could achieve relatively higher coverage and consumption than reported in other urban areas. In order to achieve the optimum level, it is imperative to equip the AWWs with current knowledge and skills, and design innovative Information, Education and Communication (IEC) campaign to target the less compliant groups. The beneficial effect of this delivery strategy may be used in similar urban settings to achieve the elimination of LF.